Real‐world implications of nonbiological factors with staging, clinical management, and prognostic prediction in pancreatic ductal adenocarcinoma - Chao Wang; Haoda Chen; Xiaxing Deng; Wei Xu; Baiyong Shen (Cancer Medicine, 2023)
Abstract Background The American Joint Committee on Cancer (AJCC) tumor‐node‐metastasis (TNM) staging system focuses on traditional biological factors (BFs). The present study incorporates nonbiological factors (NBFs) into the AJCC‐TNM staging system in terms of the advanced clinical management and prognostic‐prediction accuracy of pancreatic ductal adenocarcinoma (PDAC). Methods Eight thousand three hundred and thirty eligible patients with PDAC were obtained from Surveillance, Epidemiology, and End Results database between January 1, 2011, and December 31, 2015. Multivariate Cox proportional hazards regression analysis and Kaplan–Meier curves were used to testify the feasibility of cancer‐specific survival (CSS) prediction based on TNM‐NBF stages. Results The large population‐based study demonstrated that NBFs (insurance status, marital status, county‐level median household income, and unemployment) were significant prognostic indicators (p < 0.005), and multivariate Cox regression analysis demonstrated that the NBF1 stage carried a 29.4% increased risk of cancer‐specific mortality than NBF0 stage (p < 0.001). The concordance index of TNM‐NBF stage was 0.755 (95% confidence interval: 0.740–0.769). Conclusions The novel NBF stage was independently associated with CSS of PDAC. In addition, combining TNM with the NBF stage could provide better clinical management and prognostic‐prediction accuracy.